Revitalizing Cultural Heritage through Experiential Learning: A Participatory Action Research on Traditional Games among Generation Z Students - Risma Novita Sari; Durrotunnisa (Transformatif: Jurnal Pengabdian Masyarakat, 2025)
This study explores the use of traditional games as a culturally grounded strategy to promote character development and cultural preservation among Generation Z students. Responding to the growing dominance of digital gaming and the erosion of local values, the project was implemented at SMPN 27 Sigi, Central Sulawesi, through a Participatory Action Research (PAR) approach. The program was integrated into a school-based class meeting activity and involved three traditional Kaili games: tilako, sopu, and estafet sarung. Data were collected through observation, informal interviews, and reflective evaluation involving students, teachers, and school leaders. The findings indicate that traditional games function not only as recreational activities but also as effective experiential learning tools that foster teamwork, communication, empathy, discipline, and responsibility. Students demonstrated high levels of engagement, supported by the strategic use of social media and strong institutional collaboration. Importantly, the study reveals that deeper cultural engagement is achieved when activities prioritize quality over quantity and are supported by clear procedural design. This research contributes to the discourse on culturally responsive pedagogy by demonstrating that integrating local cultural practices into school activities can enhance both social learning and cultural awareness. The PAR-based framework also highlights the replicability of such interventions across different educational contexts, offering a practical model for sustaining cultural heritage in the digital era.